2012
DOI: 10.1029/2011wr011518
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and event dynamics of spatial soil moisture patterns at the small catchment scale

Abstract: [1] Our understanding of short-and long-term dynamics of spatial soil moisture patterns is limited due to measurement constraints. Using new highly detailed data, this research aims to examine seasonal and event-scale spatial soil moisture dynamics in the topsoil and subsoil of the small spruce-covered Wüstebach catchment, Germany. To accomplish this, univariate and geo-statistical analyses were performed for a 1 year long 4-D data set obtained with the wireless sensor network SoilNet. We found large variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
227
6
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 281 publications
(277 citation statements)
references
References 72 publications
(141 reference statements)
24
227
6
1
Order By: Relevance
“…Compared with topsoil, temporal dynamics in deeper soil layers were diminished due to lower infiltration of precipitation and to root water uptake (Rosenbaum et al, 2012). Due Note: TWI represents topographic wetness index; the canopy length was measured perpendicularly to the contour and the canopy width was measured along with contour.…”
Section: Vertical Variation In Smc In the Semi-arid Loess Plateaumentioning
confidence: 99%
“…Compared with topsoil, temporal dynamics in deeper soil layers were diminished due to lower infiltration of precipitation and to root water uptake (Rosenbaum et al, 2012). Due Note: TWI represents topographic wetness index; the canopy length was measured perpendicularly to the contour and the canopy width was measured along with contour.…”
Section: Vertical Variation In Smc In the Semi-arid Loess Plateaumentioning
confidence: 99%
“…This indicates that only when the rainfall intensity is high enough can the soil water content at depths of more than 100 cm increase remarkably or quickly. Additionally, the soil water content at a depth of 60 cm in May was generally greater than that in March, which suggested that evaporation was less able to influence the deep soil layer with the onset of the rainy season and intermittent rains could make the soil water content at depths less than 60 cm change with the seasons [20,53], forming an annual cycle similar to a cosine curve (Figure 5a). However, soil water content and shallow groundwater table tend to be steady values when the rainfall was more intense or heavier.…”
Section: Combined Effects Of Rainfall and Water Table Depth On Soil Wmentioning
confidence: 98%
“…The differences between Figure 4a,b suggested that the soil water content was more sensitive to rainfall than evapotranspiration and that the effects of rainfall could reach deeper soil layers. Therefore, soil water contents above the 20 cm depth are essentially controlled by rainfall and evapotranspiration [20] and those below the 40 cm depth are mainly controlled by rainfall and shallow groundwater in this field. during the 12-day evaporation period.…”
Section: Effect Of Rainfall On the Soil Water Contentmentioning
confidence: 99%
See 2 more Smart Citations